Conceptual analysis of federal policy discourses for upper secondary school teachers in Mexico - Aguilar Nery, Jesús (Education Policy Analysis Archives, 2022)
The conceptualization of the teaching policy on upper secondary schools in Mexico between 1982 and 2018 is analyzed, with the aim of investigating its emergence and its displacements, as well as the model of teacher development that has prevailed and glimpses into consequences for the present. Based on tools of conceptual analysis of discourses and teacher training models, it is argued that technical rationality and a “deficit” model have prevailed. It is argued that most federal programs and actions have been characterized more by updating policy or training courses and less by a contextualized, systematic, and collective reflection training process from schools. Therefore, it is necessary to establish a teacher education and professional development system that considers the trajectory, working and contracting conditions, and teacher preparation in an articulated and sustained process over time.